Management mechanisms, deterrence measures and public finance regulatory compliance in Uganda. Issue 2 (3rd June 2019) - Nkundabanyanga, Stephen Korutaro; Nakyeyune, Gorettie Kyeyune; Muhwezi, Moses
Abstract : Purpose: Despite the advancement of the assumptions of agency and institutional theories whereby monitoring structures and controls form the basis of management, inadequate public finance regulatory compliance among public entities has continued to be a challenge. The purpose of this paper is to examine how to break out of the apparent cycle of failures to comply with public finance regulations. Design/methodology/approach: A cross-sectional study that integrates two approaches (cooperative and coercive models) drawing from the view that in central government agencies, there may be stewards and also agents motivated by self-interest, suggesting that the most promising framework is that which renders the traditional ways of achieving regulatory compliance to be supplemented with the stewardship model. Thus, the authors focus on four variables: management mechanisms, ethical climate, deterrence measures and public finance regulatory compliance all drawn from agency, institutional and stewardship theories. The authors collect data from 67 central government agencies in Uganda using a structured questionnaire. Findings: The authors find that management mechanisms dimensions of leadership support and organisational commitment significantly associate with public finance regulatory compliance and so too are deterrence measures particularly oversight organs, penalties and procedural justices. Research limitations/implications: Public finance regulatory compliance can be improved through management mechanisms and deterrence measures. Originality/value: The study generates empirical evidence on the applicability of stewardship theory in the management of public entities for regulatory compliance